Trade restrictions and conflict commodities: market reactions to regulations on conflict minerals from the Democratic Republic of the Congo - Seitz, W (University of Oxford, 2012)
In this paper, I use an event study approach to investigate the claim that conflict minerals legislation in the United States (US) led to a ban on some mining exports from the Democratic Republic of the Congo (DRC), and that the passage of US regulation caused a ban on both production and trade by regulators in the DRC several months later. I also consider the assertion that conflict minerals legislation imposed severe costs for companies that report to the Securities and Exchange Commission in the US. I find that returns for some companies traded on US stock exchanges were sensitive to changes in production in the DRC after the proposed legislation became law in the US. This either suggests that some financial market participants did not expect an immediate full embargo on newly-regulated Congolese mining and trading activities, or that market participants did not expect trade to be halted indefinitely. Reactions to a DRC-imposed ban on production were statistically significant; indicating that additional reductions in trade were not fully anticipated by financial market participants after regulations became law in the US. I also find that among metal and gold mining companies traded on US exchanges, returns were abnormally high when conflict mineral legislation became more probable. Electronic communication manufacturing firms, which as a group were a target for many supporters of conflict mineral regulations, experienced no systematically abnormal returns corresponding to important dates in the US legislative process that I consider, but experienced abnormally positive returns coinciding with the ban on mining in the eastern DRC.